2013
DOI: 10.1093/neuonc/not057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of valproic acid on seizure control and on survival in patients with glioblastoma multiforme

Abstract: Polytherapy with VPA and LEV more strongly contributes to seizure control than does either as monotherapy. Use of VPA together with chemoradiation with temozolomide results in a 2-months' longer survival of patients with GBM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
156
2
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(171 citation statements)
references
References 30 publications
5
156
2
4
Order By: Relevance
“…No significant difference in terms of PFS was observed. In the study performed by Kerkhof et al [16] patients with GBM using VPA in combination with TMZ/RT showed a longer median survival of 69 weeks compared with 61 weeks in the group without VPA after adjusting for age, extent of resection and MGMT methylation status. Another study [15] has reported that VPA use during RT for GBM was associated with improved OS, independently of RTOG, RPA class, seizure history and concurrent TMZ use.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…No significant difference in terms of PFS was observed. In the study performed by Kerkhof et al [16] patients with GBM using VPA in combination with TMZ/RT showed a longer median survival of 69 weeks compared with 61 weeks in the group without VPA after adjusting for age, extent of resection and MGMT methylation status. Another study [15] has reported that VPA use during RT for GBM was associated with improved OS, independently of RTOG, RPA class, seizure history and concurrent TMZ use.…”
mentioning
confidence: 95%
“…Some retrospective clinical studies [4,[14][15][16] and a meta-analysis of individual patient data [17] have suggested that VPA could prolong overall survival in adult patients with GBM. Oberndorfer and collegues [4] investigated the effects of EI-AEDs or non-EIAEDs on survival in 168 patients with GBM treated with surgery, radiotherapy and chemotherapy (either CCNU or TMZ).…”
mentioning
confidence: 99%
“…Besides, it seems preferable to avoid AEDs on which there are hardly any data available in brain tumors. For that reason, the monotherapy drugs of first choice are the evidence-based agents levetiracetam and valproic acid for focal epilepsy and for which use in EBT many data are available (Hildebrand et al, 2005;Oberndorfer et al, 2005;Lim et al, 2009;van Breemen et al, 2009;Merrell et al, 2010b;Weller et al, 2011;Kerkhof et al, 2013;Vecht et al, 2014).…”
Section: Antiepileptic Drug Therapymentioning
confidence: 99%
“…In GBM, about 40-45% of patients present with epilepsy, often as secondary generalized seizure, while 15-20% develop seizures later on (Moots et al, 1995;Kerkhof et al, 2013). Smaller tumors and those growing less quickly are associated with higher rates of seizures than large, rapidly growing lesions (Moots et al, 1995;Glantz et al, 2000;Herman, 2002;Pasquier et al, 2002;Rosati et al, 2009;Chaichana et al, 2009b;Lee et al, 2010).…”
mentioning
confidence: 99%
“…More recently it has been appreciated that VPA is a histone deacetylase inhibitor (HDACi) [11]; these have been explored as candidate radio-sensitizers in a variety of cancers [12]. Retrospective data from trials of specific HDACis and specifically with valproate in brain cancer patients have suggested efficacy [13][14][15][16].…”
mentioning
confidence: 99%